Simple and Complex Phonic Tics in Tourette Syndrome - José Fidel Baizabal-Carvallo; Joseph Jankovic (Brain Sciences)
Tourette syndrome (TS) is the most common cause of tics. Tics are classified as motor and phonic tics. The latter (previously also referred to as “vocal tics”) are manifested by simple sounds (simple phonic tics) or complex, often semantically meaningful utterances (complex phonic tics). Methods: We compared the clinical and demographic features of consecutive patients with TS who exhibited simple and complex phonic tics. Results: There were 149 patients, 117 (78.5%) of whom were males; the mean age at evaluation was 19.61 ± 12.97 years. In total, 35 (23.5%) of these manifested complex phonic tics, and 26 (17.4%) had verbalizations. No statistically significant differences were observed between TS patients with simple versus complex phonic tics with respect to sex, age at onset, age at presentation, or comorbid attention-deficit/hyperactivity disorder or obsessive–compulsive disorder. Patients with complex phonic tics more frequently had trunk tics (p = 0.002), complex motor tics (p < 0.001), copropraxia (p = 0.002), a wider variety of phonic tics (p < 0.001) and greater tic severity (p = 0.001). The multivariate regression analysis showed an independent association between trunk tics and complex phonic tics. Conclusions: Complex phonic tics seem to be part of a more widely distributed, severe, and complex presentation of TS, likely representing a continuum within the spectrum of motor and phonic tics.